Cover Image, Volume 173A, Number 1, January 2017. Issue 1 (January 2017) - O'Byrne, James J.; Ryan, Helen; Murray, Dylan J.; Regan, Regina; Betts, David R.; Murphy, Nuala; Casey, Jillian P.; Lynch, Sally A.
Abstract : The cover image, by James J. O'Byrne et al., is based on the Clinical Report Bicoronal and metopic craniosynostosis in association with a de novo unbalanced t(2;7) chromosomal translocation, DOI:10.1002/ajmg.a.38001 .